Evaluation of Oxygen-Enhanced MRI for the identification of hypoxia induced treatment resistant tumours in patients with head and neck cancer - McCabe, Alastair (2025)
Tumour hypoxia is a recognised cause of radiotherapy treatment resistance in head and neck squamous cell carcinoma (HNSCC). Although potential hypoxia modification therapeutic strategies exist, they are not widely used in clinical practice in part due to a lack of a readily available method to identify patients who may benefit from such treatments. Imaging of tumour hypoxia is an appealing solution to this issue due to its ability to repeatedly provide information on the spatial distribution of oxygen. This thesis evaluates the potential use of the hypoxia imaging technique of oxygen-enhanced MRI (OE-MRI) for the assessment of tumour hypoxia in HNSCC.